BIOACCUMALATION AND BIOMEGNEFICATION STUDY OF THE PLANTS OF AL-CHIBAYISH MARSH, SOUTHERN IRAQ - Mouhamad, Raghad S.; AL-Gburi, Hind F.; Rasheed, Ayad G.; Razaq, Ibrahim; AL-Lafta, Hadi S. (Iraqi Journal of Science, 2019)
An aggregate of 30 samples (water, sediments, and plants) was collected from Al-Chibayish Marsh, located in Dhi-Qar Governorate southern of Iraq to investigate the bioaccumulation and biomagnification in marsh plants (flora) and to assess the marsh plants pollution condition. The study was conducted by testing the macro elements, microelements, heavy metals, and organic compositions in water, sediments, and plants. Plant analyses revealed that the Salvinia natans plant species had the highest concentrations of macroelements Mg, Ca, Na, P, and N compared with other marsh plants and sediments. As a result, the cation binds itself to be more than one charged cationic site and this behaviour was observed in Salvinia natans sp. which has the highest organic composition (protein, fibre, oil, ash, carbohydrate) reaching 30% compared with marsh plants species. Due to the leaching effect it appeared to be more involved in the dissolution of the minerals and in the binding process, since the percentage of the heavy metals (Fe, Cu, Zn, Mn, and Mo) concentrations was reached to 51%. In our results, we found that the microelements tend to be the highest percentage (68%) in the Ceratophyllum sp. compared to other plants Sp. and sediments. Accumulation of heavy metals was highest in Vulgaris (10%), and there was 5%, 9%, 4%, 4%, 5%, and 8% in Salvinia natans, ceratophyllum, Schoenoplectus litoralis, Typha australis leaves, Typha australis roots and sediments, respectively. The study also shows that the mean concentrations of microelements and heavy metals were in the order of Fe> Mn> As> Se> Pb> Cu> Zn> Mo> Ni> Cr> Cd> Li> Co. The concentrations of microelements and heavy metals in plant samples were much greater than the concentrations in water samples of Al-Chibayish Marsh (these water samples were taken from the same locations of plant samples). This is a clear indication of bioaccumulation and biomagnifications of micro elements and heavy metals in plant tissues.